The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.4049/jimmunol.0801037
|View full text |Cite
|
Sign up to set email alerts
|

Free Bone Graft Attenuates Acute Rejection and in Combination with Cyclosporin A Leads to Indefinite Cardiac Allograft Survival

Abstract: We report on a novel approach aimed at preventing acute vascular rejection (AVR), one of the major unresolved hurdles of clinical transplantation. In a C3H-to-BALB/c heterotopic heart transplant model, we demonstrate that free bone transplantation combined with cyclosporin A suppresses antidonor Ab responses, induces indefinite cardiac allograft survival (>100 days), and preserves graft architecture. In contrast, untreated- or cyclosporin A alone-treated recipients rejected their cardiac grafts on days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
2
3
0
Order By: Relevance
“…Based on this, we hypothesised that these CBFs could have an innate immunomodulatory activity partially related to MSC content. In support of this hypothesis, immunosuppressive effects of allogeneic bone grafts have been previously reported in several independent animal studies 15 17 . The aim of this study was, therefore, to examine the immunomodulatory capacity of these CBFs without any manipulation or MSC expansion, in co-cultures with allogeneic CD3/CD28-stimulated CD4 T cells.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Based on this, we hypothesised that these CBFs could have an innate immunomodulatory activity partially related to MSC content. In support of this hypothesis, immunosuppressive effects of allogeneic bone grafts have been previously reported in several independent animal studies 15 17 . The aim of this study was, therefore, to examine the immunomodulatory capacity of these CBFs without any manipulation or MSC expansion, in co-cultures with allogeneic CD3/CD28-stimulated CD4 T cells.…”
Section: Introductionsupporting
confidence: 58%
“…As such, these clinically available cellular allografts can be considered as a potential novel immunotherapy tool. As stated, several animal model studies have previously reported the ability of allogenic bone to prevent the rejection of transplanted organs 15 , 17 . In this context, our study demonstrated that clinically used CBFs could provide an ‘immuno-privileged niche’ capable of controlling adaptive immune cell responses in the allogeneic settings.…”
Section: Resultsmentioning
confidence: 96%
“…In contrast, VCA without a vascularized bone component, such as VSM, or even VSM combined with low dose donor BMC transfusion (equivalent of femur bone marrow cells), only exhibited transient, lower-level MC in periphery blood, and failed to prevent allograft acute rejection. Similar studies were reported by multiple groups using bone graft transplantation ( 43 , 52 , 53 ) or vascularized bone marrow transplantation ( 33 , 36 , 37 ) to induce hematopoietic chimerism and allograft tolerance.…”
Section: Discussionsupporting
confidence: 78%
“…Although basic research has shown that free bone co-transplantation combined with conventional immunosuppression can induce immunologic tolerance and extend allograft survival (33)(34)(35)(36)(37), in this study tolerance was not achieved and was not the target of therapy. However, regulatory effects of BF-BM on the immune system could still be identified.…”
Section: Discussionmentioning
confidence: 78%